APPEARANCE SAYS IT ALL; A RARE CASE OF HYPOHIDROTIC ECTODERMAL DYSPLASIA - Kumar, Jasvindar; Ahmed, Atif; Hussain, Taimoor; Kumar, Daneet; Aslam, Taimur (Journal of Ayub Medical College Abbottabad, 2022)
Ectodermal Dysplasia (ED) is a rare genetic condition characterized by the involvement of ectoderm derivatives such as hair, nail, sweat glands, and teeth. It has many variants, but the two most common ones are hypohidrotic/anhidrotic ectodermal dysplasia and hidrotic ectodermal dysplasia. Herein, we present a case of a 20-year-old female with hypohidrotic ectodermal dysplasia who had anodontia, hypohidrosis, and hypotrichosis, and her condition went unrecognized until she was seen for gastroenteritis at a tertiary care center. This case report will help spread education and awareness regarding such a rare and under-recognized condition. Early diagnosis and intervention help improve the quality of life.